Translation of the Passive Voice from English into B/C/S - Adilović Lubić, Amina (MAP Education and Humanities, 2022)
The passive voice is generally overused in English, hence the need to investigate how it translates to other languages, B/C/S in particular. It is also widely used in academic and business English in order to make the text diplomatic and objective, as it is preferable for business. The aim of this paper is to determine whether passive in business English texts remains intact after translation to B/C/S, and whether it plays a more central role in English or in B/C/S. After gathering data from 30 different academic articles related to economics, 63 passive structures were selected and analyzed. Subsequently, a comparison was made between them and their B/C/S counterparts in order to determine how many were translated literally to B/C/S, how many preserved the voice but changed the form, and how many samples changed both voice and form. It was discovered that 17 samples were translated literally to B/C/S, 25 retained their voice but changed the form, and 21 samples retained neither voice nor form. Based on the results obtained we have come to an expected conclusion that passive is not as present in B/C/S as it is in academic and business English, thereby it plays a more central role in English than it does in B/C/S. Interestingly, there were two examples where voice transformation was reversed, the B/C/S passives became English actives. We find such occurrences unusual, as the passive voice is typically more common in English than in B/C/S.